HUBUNGAN NASAL INDEX DENGAN FUNGSI RESPIRATORI HIDUNG : SEBUAH TINJAUAN SISTEMATIS - Advin, Tesya; Hafiz, Al; Revilla, Gusti (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Background : Nasal Index is one of the anthropometric parameters of the nose. Many studies have established the applicability of nasal index to categorize racial, gender and age variations. However, there are still few studies that have determined whether physiological differences are associated with variations in nasal index. The purpose of this study was to assess the relationship between nasal index with nasal respiratory function. Method : This research is a systematic review. The sources of databases used are Pubmed, Proquest, Science Direct, and BMC in the 2012-2022 period. Articles are selected based on predetermined eligibility criteria. The primary articles identified were screened using the PRISMA method, resulting in 10 studies included in the systematic review. Result : 4 out of 10 studies stated that nasal morphology generally affects nasal respiratory function. 3 studies found an association between nasal index and nasal air condition regulation, and 1 study found an association between nasal index and airflow and nasal resistance. The other 6 studies explained that there was no relationship between nasal index and nasal respiratory function, either in differences in airflow and nasal resistance or in the regulation of nasal air conditions. Conclusion : There is no significant relationship between nasal index and nasal respiratory function.